Executive Compensation, Macroeconomic Conditions, and Cash Flow Cyclicality - Stefano Colonnello (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2016)
I model the joint effects of debt, macroeconomic conditions, and cash flow cyclicality on risk-shifting behavior and managerial pay-for-performance sensitivity. I show that risk-shifting incentives rise during recessions and that the shareholders can eliminate such adverse incentives by reducing the equity-based compensation in managerial contracts. I also show that this reduction should be larger in highly procyclical firms. Using a sample of U.S. public firms, I provide evidence supportive of the model's predictions. First, I find that equity-based incentives are reduced during recessions. Second, I show that the magnitude of this effect is increasing in a firm's cash flow cyclicality.
urn:nbn:de:gbv:3:2-53336
Keywords: G32; J33; M52; 330; risk-shifting; executive compensation; business cycle